'I will not share my partner': The 'care of the self' in an HIV prevention campaign. (1st March 2017) - Segopolo, Irene M.; Tomaselli, Keyan G.
This article presents a textual examination and reception analysis of a HIV/AIDS poster used by the University of KwaZulu-Natal students during 2006–09. It examines how discourses construct self-responsibility for sexual health among female students. Discourse analysis, language and visual strategies are applied to reveal gender stereotypes. The article argues that an alternative discourse of femininity is used centring on female power bordering on active participation through the use of the discursive self 'I' in order to promote self-surveillance and individual agency.